PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PKn DENGAN MENGGUNAKAN MODEL TEAM QUIZ DI KELAS V SEKOLAH DASAR - Siregar, Maradoli; Hamimah, Hamimah; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research is motivated by the low of student learning outcomes in class V SD Negeri 13 cingkariang Kec.Banuhampu Kab.Agam.This study aim to describe the improvement of student learning outcomes on learning Civics by applying the model Team Quiz learning on the fifth grade students SD Negeri 13 Cingkariang Kec.Banuhampu Kab.Agam .The type of this research is PTK by using qualitative and quantitative approach. The result of student learning cycle I 73,93 increased to 82 in cycle II. It mean, the learning of Civics by applying the Team Quiz model on can improve the learning outcomes of Civics students grade V SD Negeri 13 cingkariang Kec.Banuhampu Kab.Agam